Padronização de técnica manual para obtenção de plasma rico em plaquetas de bovino - Pizauro, Lucas J. L. [UNESP]; Silva, Daniela G. da [UNESP]; Santana, Andre M. [UNESP]; Morais, Stella M. A. [UNESP]; Benincasa, Natlia C. [UNESP]; Fagliari, Jose J. [UNESP] (Revista Pesquisa Veterinaria Brasileira, 2014)
To evaluate the biochemical profile and protein concentration of whey from milk samples of healthy Murrah primiparous and pluriparous buffaloes, 30 female buffaloes were analyzed during a complete lactation. The animals were divided into three groups: G1 = 10 primiparous buffaloes, G2 = 10 pluriparous buffaloes with 2-3 lactations and G3 = 10 pluriparous buffaloes with > 3 lactations. The lactation period was divided into: early stage (I: 1-3 months of lactation), intermediate stage (T: 4-6 months of lactation) and final stage (F: 7-9 months of lactation). Before milk sampling, physical examination of the mammary gland, strip cup test and California Mastitis Test (CMT) were performed. After mammary quarters asepsis, 20mL of milk were collected monthly from each mammary quarter, during a complete lactation, in sterilized plastic bottles without preservative, in order to perform microbiological isolation, biochemical profile and protein electrophoresis in sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE), and 30mL of milk from each mammary quarter were collect, in sterilized plastic bottles containing preservative bronopol to perform the somatic cell count (SCC). A total of 1,042 milk samples were collected from the experimental groups during lactation, of which 923 samples showed negative reaction to CMT and negative microbiological isolation and were selected to biochemical profile analysis and protein electrophoresis in SDS-PAGE. There were influence of parity order and stage of lactation in biochemical profile and protein concentration of healthy Murrah buffaloes'whey. Primiparous buffaloes (G1) showed higher gamma-glutamyltransferase (GGT: 2,346 U/L), alkaline phosphatase (ALP: 181 U/L), phosphorus (P; 56.6mg/dL), potassium (K; 32.0mg/dL) and alpha-lactalbumin (458mg/dL). Buffaloes with 2-3 lactations (G2) showed higher SCC (70,700 cells/mL) and higher concentrations of total protein (1.55g/dL), albumin (100mg/dL), magnesium (Mg; 8.80mg/dL), chlorides (Cl; 176mg/dL), iron (Fe; 10.7 mu g/dL), sodium (Na; 178mMol/L) and lactoferrin (59.5mg/dL). Bufalloes with > 3 lactations (G3) showed higher concentrations of total calcium (Ca; 41.8mg/dL), ionized calcium (iCa; 2.92mMol/L), immunoglobulin A (IgA; 1.32mg/dL), serum albumin (99.1mg/dL), immunoglobulin G (IgG; 49.7mg/dL) and beta-lactoglobulin (1,068mg/dL). During lactation it was observed increase in SCC, GGT, ALP, total protein, albumin, P, Mg, Cl, Na, lactoferrin, serum albumin, IgG and alpha-lactalbumin, as well as decrease in concentrations of Ca, Fe, iCa, K, IgA and beta-lactoglobulin in buffaloes'whey. The results may be used as reference for buffaloes and to support diagnosis and prognosis of diseases common to lactation periods.

Para padronização de uma técnica manual para a obtenção de plasma rico em plaquetas (PRP) autólogo em bovinos com custo reduzido (método manual) e de boa qualidade (capacidade de concentrar plaquetas, alta concentração de fatores de crescimento e contaminação reduzida com leucócitos e eritrócitos), que poderá ser utilizado como um agente modulador da resposta imune de vacas com diferentes enfermidades, 450 ml de sangue total de nove vacas clinicamente saudáveis e com perfil hematológico normal foi coletado em bolsas de sangue CPDA-1 e processado dentro de quatro horas após a coleta. O sangue foi separado em alíquotas para avaliar 8 protocolos (P) de centrifugação dupla que variaram quanto a velocidade e o tempo de centrifugação. A contagem de plaquetas, eritrócitos e leucócitos na suspensão obtida (PRP) foi realizada pelo método manual em câmara de Neubauer: P5 (400g e 800g ambos durante 10 min) foi o protocolo com maior número de plaquetas, seguido por P3 (120g e 473g ambos durante 10 min), P4 (300g e 640g durante 10 min cada), P6 (640g durante 10 min e 640g durante 5 min), P8 (640g durante 5 min e 120g durante 10 min) e P7 (720g e 720g durante 5 min) e diferentes (p<0,05) dos menores valores encontrados em P1 (120g e 240g, ambos por 5 minutos) e P2 (120g e 473g ambos por 5 min). Em relação aos eritrócitos, P8, P7, P6, P5 e P4 apresentaram menores concentrações e maiores valores (p<0,05) foram observados em P3 e P2. Menores quantidades de leucócitos foram observadas em P5 , P6, P8 e P7 com o maior valor obtido em P2 (p<0,05). Todos os protocolos (P1 a P8) foram eficientes em concentrar plaquetas sendo o valor mais baixo (3,65±0,79) observado em P1. Em relação aos fatores de crescimento ao se mensurar TGF- 1, os protocolos P1 e P8 evidenciaram valores mais elevados. De acordo com os resultados obtidos os protocolos P5 e P8 apresentaram os melhores resultados para confecção de PRP bovino.
Biochemical profile, including protein concentration, of whey from healthy primiparous and pluriparous buffaloes during lactation
Keywords: Bubalus bubalis; Mammary gland; Somatic cell count (SSC); stage of lactation; SDS-PAGE; PRP; Concentrado de plaquetas; Terapia celular; Fatores de crescimento; TGF-β1; Bovinos